SLOPE STABILITY ANALYSIS OF IN PIT DUMP KRESNA PT ARUTMIN INDONESIA SITE SATUI USING FINITE ELEMENT METHOD - Rinelly, Shiva
PT Arutmin Indonesia Tambang Satui plans to do overburden in pit dumping on the lowwall slopes of the mined Kresna Pit to save on transportation costs. However, dumping at the Kresna Pit lowwall is difficult due to piling loose material on an inclined surface. Also, the Kresna Pit was already filled in water due to a delay in the mining process. Therefore, a safe embankment slope analysis is carried out to prevent landslides in the area. Slope stability analysis is performed using the finite element method using Phase2 8.0 software. A model of embankment slope on incline surface is created, physical and mechanical properties of the material also static load from mining equipment obtained from the company are inputed , the value of the safety factor in this method is approximated by the Strength Reduction Factor (SRF) value. If the embankment model has an SRF value of < 1.1 then the model is unsafe, and needs to be redesigned. When then having an else if an SRF value of ? 1.1 is considered to be safe. Based on the simulation result, it can be suggested the stages of in pit dumping process at cross-section A-A' are as follows: In pit dumping begins at an altitude of 8.8 m from the water sump elevation with the crest dumping method using the help of a dozer until reaching the bench width up to 19.5 m and a slope will be 30o (angle of repose). After that, dumping process by dozing can be continued even sliding is occurred due to the embankment toe entering water (but it will be stable after reaching the slope of 10o-6o) until reaches the highwall. Then, if the lifting is needed, in pit dumping can be done by increasing the embankment until a height of 10 m and a slope of 30o after lower bench reaching width of 65.1 m.